Sonographic Estimated Fetal Weight and Cesarean Delivery among Nulliparous Women with Obesity - Dude, Annie M.; Davis, Berkley; Delaney, Katie; Yee, Lynn M. (American Journal of Perinatology Reports, 2019)
Objective This study was aimed to examine the association between having an ultrasound estimate of fetal weight (US-EFW) and mode of delivery among obese women.Study Design A retrospective cohort study of nulliparous women with a body mass index of ≥ 35 kg/m2 who delivered term singleton gestations. We examined whether having had an US-EFW within 35 days of delivery, or an US-EFW ≥ 90th percentile for gestational age, was associated with intrapartum cesarean delivery.Results Of 2,826 women, 22.5% (n = 636) had an US-EFW within 35 days of delivery. Having an US-EFW was associated with increased frequency of cesarean (43.1% for those with an US-EFW versus 30.0% for those without, p < 0.001); this finding persisted when controlling for confounders (adjusted odds ratio [aOR] 1.48, 95% confidence interval [CI] 1.21–1.81). Of the 636 women with an US-EFW, 22.5% (n = 143) had an US-EFW ≥ 90th percentile for gestational age, which was associated with increased frequency of an intrapartum cesarean (60.8% for those with an US-EFW ≥ 90th percentile vs. 37.9% for those with an US-EFW of < 90th percentile, p < 0.001), even when accounting for confounders (aOR = 1.78, 95% CI: 1.10–2.87).Conclusion The presence of an US-EFW among nulliparous obese women was associated with undergoing intrapartum cesarean delivery.
Keywords: obesity; pregnancy; ultrasound; cesarean section; large for gestational age